Treating Dehydration at Home Avoids Healthcare Costs Associated With Emergency Department Visits and Hospital Readmissions for Adult Patients Receiving Home Parenteral Support. (June 2017) - Konrad, Denise; Roberts, Scott; Corrigan, Mandy L.; Hamilton, Cindy; Steiger, Ezra; Kirby, Donald F.
Background: Administration of home parenteral support (HPS) has proven to be cost-effective over hospital care. Avoiding hospital readmissions became more of a focus for healthcare institutions in 2012 with the implementation of the Affordable Care Act. In 2010, our service developed a protocol to treat dehydration at home for HPS patients by ordering additional intravenous fluids to be kept on hand and to focus patient education on the symptoms of dehydration. Methods: A retrospective analysis was completed through a clinical management database to identify HPS patients with dehydration. The hospital finance department and homecare pharmacy were utilized to determine potential cost avoidance. Results: In 2009, 64 episodes (77%) of dehydration were successfully treated at home versus 6 emergency department (ED) visits (7.5%) and 13 readmissions (15.5%). In 2010, we successfully treated 170 episodes (84.5%) at home, with 9 episodes (4.5%) requiring ED visits and 22 hospital readmissions (11%). The number of dehydration episodes per patient was significantly higher in 2010 ( P < .001) and may be attributed to a shift in the patient population, with more patients having malabsorption as the indication for therapy in 2010 ( P = .003). Conclusion: There were more than twice as many episodes of dehydration identified and treated at home in 2010 versus 2009. Our protocol helped educate and provide the resources required to resolve dehydration at home when early signs were recognized. By reducing ED visits and hospital readmissions, healthcare costs were avoided by a factor of 29 when home treatment was successful.